Phytochemical Screening and Antibacterial Activity of the Ethanolic Stem Bark Extract of Eucalyptus Camaldulensis - Raymond Iorhemen; Samuel Adawara; Gambo Gulanda (Journal of Chemistry Letters)
In this study, the stem bark of Eucalyptus camaldulensis was subjected to preliminary phytochemical and anti-bacterial analysis. The extraction of the stem bark was done with ethanol with a recovery of 12.1 %. The phytochemical evaluation, as well as the antibacterial analysis of the ethanolic leaf extract, was carried out. The phytochemical analysis showed the presence of carbohydrates, terpineol, cardiac glycoside, flavonoids, tannin, and corderoites. The antibacterial analysis of the ethanolic extract showed activity on Staphylococcus aureus, Streptococcus pyrogens, E-coli, and Pseudomonas aeruginosa at different concentrations. Eucalyptus camaldulensis possesses medicinal value owing to the presence of important phytochemicals as well as inhibitory potential against some selected microbes. Also, Eucalyptus camaldulensis could be exploited in the treatment of diseases related to the investigated microbes.